2021
DOI: 10.3389/fcell.2021.675617
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Metabolism: The Bridge Between Ferroptosis and Ionizing Radiation

Abstract: Exposure of tumor cells to ionizing radiation (IR) alters the microenvironment, particularly the fatty acid (FA) profile and activity. Moreover, abnormal FA metabolism, either catabolism or anabolism, is essential for synthesizing biological membranes and delivering molecular signals to induce ferroptotic cell death. The current review focuses on the bistable regulation characteristics of FA metabolism and explains how FA catabolism and anabolism pathway crosstalk harmonize different ionizing radiation-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 129 publications
(151 reference statements)
1
21
0
Order By: Relevance
“…As lipids are one of the major components for cellular and mitochondrial membranes, increased lipid oxidation by HG, RAD and RG supports the theory of cellular and mitochondrial membrane damage after stress [ 64 ]. Anabolic and catabolic changes in lipid and fatty acid metabolism also enhance the possibility of ferroptosis mediated cell death and mitochondrial membrane damage [ 65 , 66 ]. Glycosphingolipids are another vital component for cell and mitochondrial membranes [ 67 ], which are protected by T2E after stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As lipids are one of the major components for cellular and mitochondrial membranes, increased lipid oxidation by HG, RAD and RG supports the theory of cellular and mitochondrial membrane damage after stress [ 64 ]. Anabolic and catabolic changes in lipid and fatty acid metabolism also enhance the possibility of ferroptosis mediated cell death and mitochondrial membrane damage [ 65 , 66 ]. Glycosphingolipids are another vital component for cell and mitochondrial membranes [ 67 ], which are protected by T2E after stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that fatty acids regulate each part of the cancer lifecycle and suggests that therapeutic intervention targeting lipid and fatty acid metabolism signaling pathways by MGF holds promise for colorectal cancer treatment ( Kadochi et al, 2017 ; Nakamura et al, 2018 ; Li et al, 2021 ). Fatty acid catabolism and anabolism pathway crosstalk are pivotal in cell fate decision during redox regulated ferroptosis cancer therapy and maybe strongly context dependent ( Hassannia et al, 2018 ; Kumar et al, 2021 ; Yuan et al, 2021 ). In clinical trials, MGF treatment was already found to improve metabolic health (diabetes, hyperlipidemia, insulin resistance) by optimization of mitochondrial bioenergetic pathways (fuel switching between fatty acid and carbohydrates) via sirtuin (SIRT) and PPAR (in)dependent metabolic mechanisms ( Guo et al, 2011 ; Niu et al, 2012 ; Apontes et al, 2014 ; Na et al, 2015 ; Singh et al, 2018b ; Li et al, 2018 ; Liu et al, 2018 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, these PUFA-PLs are oxidized by another enzyme named ALOX15 into PL-PUFA-OOHs. Since PL-PUFA-OOHs can trigger ferroptotic cell death, the activity of the abovementioned enzymes contributes to the promotion of ferroptosis ( 38 ). Surprisingly, although ALOX15 and ACSL4 facilitate the ferroptosis process, recent studies showed that higher expression of these molecules was associated with increased cancer malignant features.…”
Section: Ferroptosis Regulators In Lung Cancermentioning
confidence: 99%